Vivekananda's conception of normative ethics and resolution of ethical problems in business - Guha, D. (2005)
The paper aims at unravelling the dynamics of Vedantic ethics as conceived by Vivekananda. It gives us an overview of what Vivekananda felt about the application of Vedantic ethics in resolving crises modern man faces in practical and professional life, and I have tried to read between the lines to justify a valid model of dialogue and corroboration implicit in Vivekananda's expositions which acts as an axiomatic standard of model of ethical resolution of crises in business and management. - Reproduced.
Keywords: Ethics; Vivekananda, Swami